Self-esteem and satisfaction in the workgroup. The postpandemic perspective - Miloș, Constantina-Alina; Sandu, Mihaela Luminița (Technium Social Sciences Journal, 2023)
The relationship between job satisfaction and self-esteem has been analysed at length by professionals in different fields. Research on the relationship between job satisfaction and self-esteem aims to improve worker productivity. Although research over time includes many different jobs, methods, and test groups, the conclusion is almost unanimous that regardless of job status, there is a strong relationship between job satisfaction and self-esteem. The research aim is to identify the relationship between the self-esteem of employed people and their satisfaction in the work group. In this sense, we analysed some basic concepts, self-esteem and job satisfaction - the second of its components. The values obtained during the statistical tests carried out showed the existence of a correlation in the selected sample. Such a link is vital for employers to be aware of, as work failures could negatively impact employees with low self-esteem.